AI, governance, and law: how capitalism drives culture and innovation - Pistor, Katharina (Henry Stewart Talks, 2025)
Capitalism, Open AI, Governance, Regulation, Social economics, Fannie Mae and Freddie Mac, Corporate law, State vs. federal, Co-ops, Central bank bailout